Diagnostic accuracy of computed tomography scoring index in predicting mortality among suspected patients of acute pancreatitis - Omair, Uzma; Azmat, Uzma; Rakhshani, Abdul Q (International Journal of Endorsing Health Science Research, 2021)
Background: Acute pancreatitis (AP) is challenging, varying from subtle edema to parenchymal necrosis in severity. Several clinical and radiological scoring criteria have been formulated over the years to predict the disease intensity of AP to guide monitoring and intervention. This study aimed to establish the diagnostic accuracy of high Balthazar’s computed tomography scoring index (CTSI) in predicting outcomes in terms of mortality and morbidity among suspected cases of the acutely inflamed pancreas. Methodology: A cross-sectional study was carried out at the Radiology Department of Jinnah Postgraduate Medical Center (JPMC), Karachi. A total of 1434 clinically suspected AP patients were included in this study. The initial diagnosis was made through contrast-enhanced computed tomography (CECT) of the abdomen. Balthazar's CTSI ascertained the disease severity, and outcomes were recorded in terms of survival and death. Results: The gender distribution showed a male majority, i.e. 789(55%), and most patients were in the 45-55 year age group comprising 650 patients (45.3%). Moreover, out of 1434 patients, 397(28%) died while the rest survived. This study showed that high CTSI is a prognostic indicator of mortality in suspected cases of AP. It has a sensitivity of 91.9%, specificity of 88.72%, a positive predictive value (PPV) of 94.5% and a negative predictive value (NPV) of 83.98%. Overall diagnostic accuracy (DA) was found to be 90.9%. Conclusion: It is concluded from the study results that Balthazar’s CT severity index is reliable in establishing severity and disease outcome in AP. Thus, its routine application should be encouraged for timely detection and appropriate management of AP.